2015
DOI: 10.1017/s0960258514000452
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the interpretation of temperature effects on dormancy and germination in seed populations showing dormancy

Abstract: A framework for the interpretation of temperature effects on dormancy and germination in seed populations showing dormancy. AbstractTemperature is a key factor affecting both dormancy and germination. In non-dormant seeds, when temperature is within the thermal range permissive for germination, it just regulates germination velocity, while in seeds presenting dormancy it can also be affecting dormancy level, dormancy termination and the expression of dormancy itself. This dual effect of temperature on dormancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 42 publications
4
138
0
2
Order By: Relevance
“…Temperature regulates germination in two main ways: by modulating seed dormancy, and by affecting the germination rate of nondormant seeds (Batlla & Benech‐Arnold, ). We first analyzed germination behavior of naturally dispersed Nothofagus seeds at 12, 17 and 22°C, and observed that, whereas N. obliqua and N. pumilio did not germinate in these conditions, a large proportion of N. nervosa seeds completed germination at the warmer temperatures (% germination: 22°C = 86.4 ± 3.8; 17°C =75.4 ± 3.8), although only a small fraction of the population (6 ± 0.76%) germinated at 12°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature regulates germination in two main ways: by modulating seed dormancy, and by affecting the germination rate of nondormant seeds (Batlla & Benech‐Arnold, ). We first analyzed germination behavior of naturally dispersed Nothofagus seeds at 12, 17 and 22°C, and observed that, whereas N. obliqua and N. pumilio did not germinate in these conditions, a large proportion of N. nervosa seeds completed germination at the warmer temperatures (% germination: 22°C = 86.4 ± 3.8; 17°C =75.4 ± 3.8), although only a small fraction of the population (6 ± 0.76%) germinated at 12°C.…”
Section: Resultsmentioning
confidence: 99%
“…() in which the GR of each fraction of the population is linearly related to the incubation temperature. T b is defined by the interception of the temperature axis when GR (g) = 0 (Batlla & Benech‐Arnold, ).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we demonstrate that a process that is generally overlooked in hydrothermal germination models is important for A. thaliana : temperatures ranges for germination are dynamic and thus model parameters such as optimal and supra‐optimal temperatures are not static (Batlla & Benech‐Arnold, ). These temperature ranges change during dry after‐ripening and are altered by the seed‐maturation environment.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is a critical environmental regulator of seed dormancy, signaling seasonal information to seeds to match their germination potential to periods favorable for seedling emergence and survival as well as influencing subsequent phases of the plant life cycle (Footitt et al, 2014;Batlla and Benech-Arnold, 2015;Burghardt et al, 2015;Huo and Bradford, 2015). In many crops, domestication has largely eliminated these natural dormancy mechanisms, but in others, such as lettuce, they persist and can cause problems for germination and synchronous crop establishment when temperatures exceed permissive limits .…”
Section: Discussionmentioning
confidence: 99%